Reverse mentoring and peer coaching as professional development strategies - Porras, Nohora Inés; Díaz, Lenys Smith; Nieves, Marlen María (Colombian Applied Linguistics Journal, 2018)
Presently, learning a foreign language is an essential academic requirement in several contexts, hence the importance and the need for effective teaching in this field at all educational levels starting with the first years of school. As a consequence, teaching and learning in elementary school is a key issue to success in the learner’s future language learning. However, at some public elementary schools in Colombia there are many factors that hinder this process. One of them is the fact that most of the teachers who are in charge of teaching English in elementary schools are not sufficiently trained to do this job (McNulty & Quinchía, 2007). For this reason, the aim of this study is to strengthen the pedagogical practices of the participating teachers. Guided by the theoretical foundations of peer coaching and reverse mentoring, this mixed-methods study examined strategies for professional development via results of an English test, class observations, questionnaires, focus groups, interviews, and journals. Findings show the effectiveness of the proposal in terms of the professional growth of the participants who exchanged teaching experiences and pedagogical tools within a mutual and trusting atmosphere. This helped them to enhance their knowledge about teaching a foreign language and test new teaching techniques and strategies to favor their students’ language learning.